PENGARUH HARGA, DESAIN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA BENGKEL KAYU SANTU DAMIAN CANCAR - Maria Heniko Halima; Yohana Maria Dolorosa Mahin; Yosefina Elsiana Suhartini (LPPM STIE YKPN Yogyakarta, 2025)
The purpose of this study was to analyze the effect of price, design and product quality on consumer purchasing decisions at St. Damian Cancar wood working shop partially and simultaneously. The population of this research is all the consumers of St. Damian Cancar wood working shop, with a total of 34 respondents who are used as research objects. The data were collected through questionnaires distributed to respondents and then analyzed using descriptive statistical analysis and multiple linear regression analysis with the help of the SPSS version 26 program. The results of this study state that partially the price has a positive and significant effect on purchasing decisions, product design has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on consumer purchasing decisions at St. Damian Cancar wood working shop. Simultaneously, price, design and product quality have a positive and significant effect on consumer purchasing decisions at St. Damian Cancar wood working shop.